The Lesser Prairie-Chicken range-wide conservation plan - Klute, David, speaker; Riley, Terry, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The lesser prairie-chicken (Tympanuchus pallidicinctus) is a prairie grouse endemic to the southern Great Plains where it occurs primarily on private land. In March 2014 the U.S. Fish and Wildlife Service determined the lesser prairie-chicken warranted listing as a Threatened species under the Endangered Species Act. The Western Association of Fish and Wildlife Agencies (WAFWA) developed the Lesser Prairie-chicken Range-wide Conservation Plan (range-wide plan) to set population and habitat goals, identify focal areas and connectivity zones required to sustain and expand lesser-prairie-chicken populations, and encourage coordination of habitat management activities both prior to and after the ESA listing. A novel aspect of the range-wide plan is a voluntary mitigation framework which (1) financially incentivizes avoidance and minimization of impacts from industry at broad and local spatial scales and (2) financially incentivizes the implementation of beneficial conservation practices by private landowners to offset impacts through the use of both short-term management contracts and permanent conservation easements. With the implementation of the Threatened listing, a special 4(d) rule provides incidental take coverage for activities conducted by participants in the range-wide plan. As of May 2014 over 6.2 million acres have been enrolled in the range-wide plan and associated Candidate Conservation Agreement with Assurances (CCAA). Enrollment fees of over $43 million have been committed to fund mitigation offsets in perpetuity for future impacts on enrolled acres. Contracts on private land in high-quality lesser prairie-chicken habitat are being implemented to offset impacts anticipated in 2014.
Development and implementation of the Lesser Prairie-Chicken range-wide conservation plan
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses